Rationality and Responsibility. Issue 4 (1st October 2020) - Schmidt, Sebastian
ABSTRACT : Broome takes the debate on rationality to be concerned with the ordinary use of 'rational'. I argue that this is at best misleading. For the object of current theories of rationality is determined by a specific use of 'rational' that is intimately connected to blame and praise. I call the property this use refers to 'rationalityRESP '. This focus on rationalityRESP, I argue, has two significant implications for Broome's critique of theories of rationality as reasons-responsiveness. First, rationalityRESP is plausibly conceived of as a kind of reasons-responsiveness. Secondly, Broome's dispute with internalists about normativity as well as his dispute with externalists about rationality both hinge on questions regarding the concept of responsibility. I conclude that philosophers should integrate discussions about responsibility in their debates about rationality.